A blind circadian clock in Cavefish reveals that opsins mediate peripheral clock photoreception - Cavallari, Nicola; Foulkes, Nicholas S. (PLoS biology, 2011)
Evolution during millions of years in perpetual darkness leads to mutations in non-visual opsin genes (Melanopsin and TMT opsin) and an aberrant, blind circadian clock in cavefish.
Gesehen am 19.07.2017